HERPES ZOSTER IN RA PATIENT TREATED WITH METHOTREXATE - Yu. V. Muraviev; G. I. Gridneva (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
This article describes herpes zoster (HZ) manifestation in RA patient treated with Methotrexate (MTX). The possibility of effective continuation of MTX after the symptoms of HZ resolve is demonstrated. The possibility of a causal relationship between the use of the MT and the manifestation HZ infection, and treatment options are discussed.